HOW DOES DIGITAL AGILITY ENHANCE ENTREPRENEURIAL PERFORMANCE? A SOCIO-TECHNICAL PERSPECTIVE ON DIGITAL TRANSFORMATION (Proceeding of SINERGY, 2026)
This study examines the effect of digital agility on entrepreneurial performance, with digital transformation as a moderating variable, grounded in Socio-Technical Systems (STS) theory. A mixed methods approach with a sequential explanatory design was employed. The quantitative phase involved a survey of 120 wood craft entrepreneurs in Tulungagung, Indonesia, selected using purposive sampling and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital agility and digital transformation have positive and significant effects on entrepreneurial performance, while digital transformation significantly strengthens the relationship between digital agility and performance. To enrich the quantitative findings, the qualitative phase was conducted through in-depth interviews with 12 participants, consisting of wood craft entrepreneurs, community representatives, and SME facilitators. Qualitative results reveal that performance improvement is driven by the alignment between social systems (adaptive capabilities, learning orientation, and entrepreneurial behavior) and technical systems (digital tools, platforms, and business processes). This study contributes by extending STS theory to explain socio-technical mechanisms in digital entrepreneurship within traditional craft-based SMEs.